(3GdJGQjN GdeXaQis - (3GHf CHj GdOe , EHQGgje Hf YHO Gddg Hf YHO GdefYe GdgePGfj GdMehj, GHf CHj GdOe,J (B642 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdBNQ GdXGgQ GdHGWf s
(3BNQgG (B:s
(3JfJgi HhbaI bde CKfGA MhGOK SfI (B627 (3g` HbUjOI dGHf GdHWQjb ai eOM Gdedc GdeXaQ eWdYgG CMSf Edi dejG eG Mf YGTb heG gJaJ hQbGA Ch PQ TGQb s
(3HOCg ef GdgLQI Edi SfI (B642 (3ceG ai cTa GdXfhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B53s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdCScfOQjI (B(1292(3H(B) s
Keywords: (3GdJGQjNs